Eco-friendly solid polymer electrolytes doped with NaClO4 for next-generation energy storage devices: structural and electrochemical insights - Cyriac, Vipin; Ismayil; Mishra, Kuldeep; Rao, Ankitha; Khellouf, Riyadh Abdekadir; Masti, Saraswati P.; Noor, I. M. (Royal Society of Chemistry, 2025)
One of the environmental challenges of energy storage devices is ensuring sustainable manufacturing and disposal practices to minimize hazardous waste. In this study, a blend of green polymers, chitosan (CS) and polyvinyl alcohol (PVA) is used as a host matrix to create flexible ion-conducting films, with ion donating NaClO4 added to enable ion transport. A significant polymer-salt interaction is evident from the FTIR investigations. Impedance spectra reveal a decrease in the bulk resistance with increasing salt content, highlighting the potential of the system for energy storage applications. The optimized bulk conductivity is improved from (1.43 ± 0.26) × 10−8 S cm−1 for the pure blend to (5.23 ± 0.27) × 10−4 S cm−1 for the composition with 35 wt% NaClO4. The ion transport properties, investigated using the Schutt and Gerdes (S-G) model, reveal a strong dependency of conductivity on the carrier concentration over ion mobility. Linear sweep voltammetry (LSV) showed the high electrochemical stability of PCP35 up to 2.6 V. The ionic transference number close to unity confirms the purely ionic nature of the optimized composition. The electric-double layer capacitor (EDLC) comprising the optimized electrolyte composition delivers a specific capacitance of 20.58 F g−1 at 0.05 mA g−1, with energy and power densities of 2.69 W h kg−1 and 97 W kg−1, respectively.